Machining of Printed Circuit Boards Using an Industrial Robot in a Simulation Environment - Komák Martin; Pivarčiová Elena; Herčút Patrik (Management Systems in Production Engineering)
This paper is devoted to the design, simulation, and optimization of a robotic cell designed to machining printed circuit boards (PCBs) using a stationary milling machine mounted on an industrial robot. The main goal was to create a digital model of the production workplace in the RobotStudio environment, which allows testing robot movements, program logic, and functional arrangement of the entire system prior to physical implementation. The use of offline programming reduces costs and risks, enables rapid tuning of robot paths, and minimizes collision states. An important part of the design was the creation of a custom gripper made by 3D printing. This gripper combines vacuum suction cups with pneumatic clamping, which allows gentle manipulation of PCBs without damaging electronic components. The created cell model includes a conveyor system, a milling machine, a protective Plexiglas cover, and a camera to recognize PCB types. The simulation confirmed the functionality of the entire cycle, the optimized length of which is 56.58 s. The results show the potential of digital design for automated manufacturing cells and open the space for future research in the field of effectors, advanced control, and artificial intelligence in industrial automation.